IDENTIFIKASI KESULITAN BELAJAR SISWA DALAM PEMBELAJARAN AKUNTANSI - Maharianti, Ratri; Parijo, Parijo; Purwaningsih, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract:This thesis is entitled "Identifying Student Learning Difficulties in Accounting Learning in Class XI IPS of SMA 1 Meliau in Academic Year 2018/2019". With the general problem "How to Identify Student Learning Difficulties in Accounting Learning in Class XI IPS High School 1 Meliau Academic Year 2018/2019?". The method used in this thesis is a descriptive method and the form of research used in this paper is a survey. While the data collection techniques collected are direct communication techniques, documentary studies. Data collection tools used are interviews and literature. The results of the study are as follows: 1) Learning difficulties experienced by class XI IPS students of SMA 1 Meliau in Academic Year 2018/2019 tend to experience difficulty to focus on learning, often sleepy, often day dreaming and difficult to capture and absorb the subject matter explained by the teacher in front of the class. 2) There are two factors that can cause learning difficulties, namely: internal factors (internal factors) and external factors (external factors). However, it is important to remember that the main factors influencing students learning difficulties is interna. 3) the Identification of student learning difficulties in accounting learning in class XI IIS SMA 1 Meliau in the Academic Year 2018/2019 is positive as seen from the results of observations and interviews the average student in experiencing learning difficulties, namely the understanding of the material.Â Keywords: Identify Student Learning Difficulties, Accounting Learning.Â